Influence of High and Low Levels of Plant-Beneficial Heavy Metal Ions on Plant Growth and Development - Arif, Namira; Yadav, Vaishali; Singh, Shweta; Singh, Swati; Ahmad, Parvaiz; Mishra, Rohit K.; Sharma, Shivesh; Tripathi, Durgesh Kumar; Dubey, N. K.; Chauhan, Devendra K. (Frontiers in Environmental Science, 2016)
Heavy metals (HMs) exists in the environment in both forms as essential and non-essential. These HM ions enter in soil biota from various sources like natural and anthropogenic. Essential HMs such as cobalt (Co), copper (Cu), iron (Fe), manganese (Mn), molybdenum (Mo), nickel (Ni), and zinc (Zn) plays a beneficial role in plant growth and development. At optimum level these beneficial elements improves the plant’s nutritional level and also several mechanisms essential for the normal growth and better yield of plants. The range of their optimality for land plants is varied. Plant uptake heavy metals as a soluble component or solubilized them by root exudates. While their presence in excess become toxic for plants that switches the plant’s ability to uptake and accumulate other nonessential elements. The increased amount of HMs within the plant tissue displays direct and indirect toxic impacts. Such direct effects are the generation of oxidative stress which further aggravates inhibition of cytoplasmic enzymes and damage to cell structures. Although, indirect possession is the substitution of essential nutrients at plant’s cation exchange sites. These ions readily influence role of various enzymes and proteins, arrest metabolism, and reveal phytotoxicity. On account of recent advancements on beneficial HMs ions Co, Cu, Fe, Mn, Mo, Ni, and Zn in soil-plant system, the present paper: overview the sources of HMs in soils and their uptake and transportation mechanism, here we have discussed the role of metal transporters in transporting the essential metal ions from soil to plants. The role played by Co, Cu, Fe, Mn, Mo, Ni, and Zn at both low and high level on the plant growth and development and the mechanism to alleviate metal toxicity at high level have been also discussed. At the end, on concluding the article we have also discussed the future perspective in respect to beneficial HM ions interaction with plant at both levels.